PENGARUH PEMBERIAN FEED ADDITIVE DALAM PAKAN SEBAGAI PENGGANTI ANTIBIOTIK TERHADAP PERSENTASE KARKAS BAGIAN DADA DAN PAHA AYAM BROILER - Mahendra, Dwi Agung; Tugiyanti, Elly; Susanti, Emmy (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. This study aims to determine the effect of giving feed additives as a substitute for antibiotics on the percentage of carcasses of the breast and thighs of broiler chickens. Materials and methods. The material was 120 DOC which were divided into 24 cage units. Maintenance was carried out on DOC starter aged 1-14, treatment from 15-35 days old. The method used was a completely randomized design (CRD), there were 4 treatments and 6 replications with treatment given 0.125% Olaquindox (R0) antibiotics, 0.2% Promix probiotics (R1), phytobiotics (0.04% garlic flour)., turmeric 0.8%, and ginger 0.8%) (R2), and Acidifier Acidtec 401 1% (R3). The variables measured were the percentage of the chest and thigh carcass. Results. The average percentage of the thigh carcass with feed treatment in the form of adding the antibiotic olaquindox 0.125% (R0) 10.65±1.08%, Promix 0.2% (R1) was 11.05±1.00%, acidifier Acidtec-401 1 % (R2) was 10.09±1.34% and phytobiotics (garlic 0.04%, turmeric and ginger were 0.8% each) (R3) were 11.24±0.76%. Conclusion. The average percentage of broiler chicken breast carcass treated with 0.125% olaquindox antibiotics was 25.30¬±1.74% (R0), Promix 0.2% probiotic was 25.56±1.39% (R1), acidifier Acidtec-401 1% was 27.28±0.98 (R2) and phytobiotics (garlic 0.04%, turmeric and ginger 0.8% each) were 26.38±1.52% (R3). The addition of feed additives in feed can replace the role of antibiotics in feed.